Head lice(Pediculus humanus capitis) infestation and the role of health education in limiting its spread among children at Primary-School in Misurata,Libya (Journal of Medical Sciences, 2022)
Pediculus humanus capitisis a worldwide scourge and children are more susceptible to infection than adults. Therefore, implementing health education programmes to control the spread of Head lice requires a great effort from teachers and parents. This study was conducted from November 2019 to February 2020 at some primary schools in Misurata city. The study community included 825 (male & female) students between the ages of 7and 12. A first test was conducted to detect the prevalence of the infection with Pediculus humanus capitisis among students and the main influencing risk factors. Another test was conducted to achieve the effectiveness of health education in reducing infection . The results of this study revealed that the number of children with Pediculus humanus capitisis was 197 i.e. (23.9%) out of the 825 examined students. This percentage has decreased to (11.5%) following the intervention of health education programmes, with a statistical significance of (P